The George Wilson Effect: Does Intergenerational Closure and Collective Efficacy Reduce Juvenile Delinquency in a Neighborhood?. Issue 12 (2nd December 2018) - Valasik, Matthew; Barton, Michael S.
ABSTRACT: A substantial amount of research found crime and delinquency to be lower in areas with stronger neighborhood communities, but the casual mechanism behind this association remains debated. The current study contributes to this debate by examining the association of two forms of social capital with rates of delinquency. The first, collective efficacy, has been widely studied, while the second, intergenerational closure has not. While the results support previous research indicating the primary role of collective efficacy as a proactive factor against delinquency, results for intergenerational closure suggest the influence of neighborhood community on delinquency does not always result in lower delinquency.